2016
DOI: 10.1038/nmicrobiol.2016.216
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Onchocerca volvulus, agent of river blindness

Abstract: Human onchocerciasis is a serious neglected tropical disease caused by the filarial nematode Onchocerca volvulus that can lead to blindness and chronic disability. Control of the disease relies largely on mass administration of a single drug, and the development of new drugs and vaccines depends on a better knowledge of parasite biology. Here, we describe the chromosomes of O. volvulus and its Wolbachia endosymbiont. We provide the highest-quality sequence assembly for any parasitic nematode to date, giving a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
180
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(188 citation statements)
references
References 111 publications
6
180
2
Order By: Relevance
“…The strategy was to use C. elegans as a reference for assigning ancestral chromosomal identity. To test if this was a valid approach, we confirmed that the chromosomal identity for most orthologs has been conserved between C. elegans and C. briggsae (for which the genome is resolved at the chromosomal level [40, 41]) and Haemonchus contortus [42]. H. contortus also has six chromosomes, but is much more distantly related to Caenorhabditis than is Caenorhabditis to Diploscapter , thus serving as an outgroup representative for these comparisons (Figures 1A, S4).…”
Section: Resultsmentioning
confidence: 99%
“…The strategy was to use C. elegans as a reference for assigning ancestral chromosomal identity. To test if this was a valid approach, we confirmed that the chromosomal identity for most orthologs has been conserved between C. elegans and C. briggsae (for which the genome is resolved at the chromosomal level [40, 41]) and Haemonchus contortus [42]. H. contortus also has six chromosomes, but is much more distantly related to Caenorhabditis than is Caenorhabditis to Diploscapter , thus serving as an outgroup representative for these comparisons (Figures 1A, S4).…”
Section: Resultsmentioning
confidence: 99%
“…The publication of the genome of O. volvulus [108] should assist this search. Means to improve coverage and compliance of CDTI and the discovery of a reliable macrofilaricide are also required, together with continuing research to find a vaccine.…”
Section: Five-year Viewmentioning
confidence: 99%
“…Advances in sequencing technologies have enabled the exploration of many new genomes across all domains of life [18]. Unfortunately, in most instances correctly aligning even just two genomes at base-pair resolution can be challenging.…”
Section: Introductionmentioning
confidence: 99%